2016
DOI: 10.1002/pros.23270
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Osteomimetic Response of Androgen‐Dependent and Independent Human Prostate Cancer Cells to Mechanical Action of Fluid Flow: Prometastatic Implications

Abstract: MAFF activated osteoblast-like phenotype of prostate cancer cells and altered their responses to osteocyte soluble factors. It also induced osteocyte production of osteomimetic gene expression- and cytokine secretion-stimulating factors for prostate cancer cells, particularly, when they were mechanically stimulated. Importantly, MAFF induced a prometastatic response in androgen-independent prostate cancer cells, suggesting the interest of mechanical stimulation-dependent transcription and secretion patterns as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…All the experimental results in this study indicate osteoblastic bone formation by PC‐3 cells and osteolytic bone resorption by MDA PCa 2b, whereas PC‐3 is predominantly identified as osteolytic and MDA PCa 2b as osteoblastic in nature based on experiments at primary sites of cancer . ex vivo studies have demonstrated the osteoblastic characteristic of PC‐3 cells in a 3D cancer–bone model using a co‐culture of live calvarial bones and cancer cells .…”
Section: Discussionmentioning
confidence: 50%
“…All the experimental results in this study indicate osteoblastic bone formation by PC‐3 cells and osteolytic bone resorption by MDA PCa 2b, whereas PC‐3 is predominantly identified as osteolytic and MDA PCa 2b as osteoblastic in nature based on experiments at primary sites of cancer . ex vivo studies have demonstrated the osteoblastic characteristic of PC‐3 cells in a 3D cancer–bone model using a co‐culture of live calvarial bones and cancer cells .…”
Section: Discussionmentioning
confidence: 50%
“…At present, a large number of drugs, including abiraterone acetate, bicalutamide and cabazitaxel have been approved by the U.S. Food and Drug Administration for the treatment of human prostate cancer (3,4). Androgen deprivation therapy has demonstrated a degree of effectiveness against androgen-dependent prostate malignancies (5,6). However, as prostate cancer advances it frequently transforms into androgen-independent prostate cancer (AIPC), reducing the efficacy of androgen deprivation therapy (7).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PCa-derived EVs have been reported to play a role in metastatic bone remodeling including favoring the differentiation of osteoblasts, impairing the differentiation of osteoclasts, and driving osteomimicry of PCa cells in the bone microenvironment [43][44][45][46][47][48]. Intriguingly, integrins that are found in the exosomal cargo can be instrumental in organ-specific metastasis [49] and the transfer of αVβ6 integrins between PCa cells was shown to promote cell adhesion and migration [50].…”
Section: Pre-metastatic Niche (Sending a Reconnaissance Team Ahead Ofmentioning
confidence: 99%